Nota crítica a dos comentarios carolingios al Arte mayor de donato. Una posible ocurrencia de scalenos - Ayuso García, Manuel (Exemplaria Classica, 2014)
The paper tries to shed light into a passage present in two edited carolingian com- mentaries on donatus’ Ars maior. the text of the manuscripts and editions offers the dark word scalineon, which is neither quoted in thll nor included in latin and greek reference dictionaries1. in our opinion, it should be read as scalenon, the geometrical figure with different angles and sides. We also propose other minor emen- dations linked to this one.